Exploring Technology Innovation Management’s Impact on Business Competitiveness and Efficiency: SmartPLS Approach - Zururi, Achmad; Andriyansah; Lesmana, Rosa; Louise, Natalia (APTISI Transactions on Management (ATM), 2025)
This study investigates the impact of Technology Innovation Management (TIM) on business competitiveness and operational efficiency, employing a SmartPLS-based structural equation modeling approach. TIM is critical for or- ganizations navigating rapidly evolving technological landscapes, enabling them to enhance innovation, differentiate themselves, and optimize resources. The research evaluates these relationships through a quantitative design, utilizing a structured survey distributed across organizations adopting TIM practices. Data from 150 respondents were analyzed to test two hypotheses: (H1) TIM posi- tively influences business competitiveness, and (H2) TIM positively impacts op- erational efficiency. Data analysis was conducted using SmartPLS, which con- firmed both hypotheses. TIM significantly enhances competitiveness (β = 0.62, p < 0.001) and operational efficiency (β = 0.71, p < 0.001). Compet- itiveness benefits include market differentiation, improved customer satisfac- tion, and agility in responding to market changes. Efficiency gains stem from streamlined processes, cost reduction, and optimized resource utilization. These findings underscore TIM’s role as a strategic enabler of sustainable business performance. The study contributes to the literature by empirically validating the relationship between TIM, competitiveness, and efficiency. Practical im- plications include recommendations for managers to prioritize TIM initiatives. Limitations, such as the cross-sectional design and sampling method, suggest avenues for future research to explore these dynamics in diverse contexts and longitudinal studies.